Gestión de calidad y su incidencia en los costos operativos de Proyectos de desarrollo y saneamiento de la constructora Razconsa C.A. de Esmeraldas, Periodo 2013 – 2014. - Córdova Montaño, Juan Carlos (2016)
Assess the impact of a system of quality management in the construction company Razconsa CA, it has determined based on the costs of construction of sanitation, which allow to determine those responsible for indicators to assess parameters field parameters that can be corrected as they happen everyday problems in project implementation, to ensure the productivity of work activities. By introducing Razconsa C.A. a system of quality management, the need for this to interact with programming production costs so that is perfect and complete the evaluation process productivity was evident, considering also that the development of processes running jobs it requires that the assessment be complemented by scheduling execution of the work. This research was necessary to determine and instruct factors management works, framed in the definitions of quality costs and not quality, through its assessment in relation to planning water projects evaluated, so that is established at any stage of the process, nonconformity and to apply adjustments to the programming of projects. This form has been developed for each instance of the process of quality control, cost analysis based on indicators that allow the evaluation of quality costs when an item of construction is well executed, and the same way with costs no quality if the items present attributable to faulty construction, poor execution of a process, rejection by a technical process is not executed considering possible severance payments, costs attributable to legal proceedings and permissions problems errors, and analysis non-tangible costs for poor quality. With cost analysis, total quality indicators of service performance waterworks running Razconsa CA. are determined, the same that determine results that are coupled to the reality of the implemented system and identifies weaknesses in its implementation, in its application and valuation in economic terms.